Development of Post-Pandemic Covid19 Higher Education Resilience Framework in Malaysia - ABDULLAH, MOKHTAR; Husin, Nor Azilah; Haider, Ameer (Archives of Business Research, 2020)
The pandemic of Covid-19 will drastically change the world. The thought and functioning of governments, organisations, and citizens will change dramatically – even for the long term. The higher education (HE) market is currently experiencing a tectonic change among many economic sectors. Following the pandemic in Covid-19, the country is home to tens of thousands of students either forced to live in the campus or deportation from the campuses and academic staff. Higher education institutions (HEI) are split up and teachers and students struggle with the new sudden law of teaching and learning completely implemented in the field of technology. How has Covid 19 pandemic altered main processes in education, including academic recruitment, academic management, teaching and learning processes, study and advancement processes, student life (accommodations on the campus, financial and co-curricular activities and other student welfare activities including food, transportation etc.)? On the other hand, how has Covid-19 compelled the institutions of HE to implement new approaches, and to let go of their current teaching practices. The benefits, drawbacks and barriers to online platforms are included. In addition, intellectual honesty is a crucial concern in the online educational network. In this paper, all the main issues described above will be addressed through the development of a conceptual framework as a response to the Covid-19 pandemic that is happening throughout the world. The framework is based on the propositions developed by Duchek (2020). In this process-based framework the issues are connected to a set of constructs that act as enablers of Higher Education Resilience (HER). The enablers or drivers of HER include ‘meta-capability’ of HE (knowledge, resource availability, social resources, and power/responsibility) and resilience stages (anticipation, coping, and adaptation). The practical application of this study is the formulation of Higher Education Resilience Index (HERI) which will help stakeholders such Ministry of Higher Education (MOHE) to categorize each HEI according to the level of HERI, as either Very Low, Low, Moderate, and High Resilience. Using the HERI categories the governments, MOHE in particular, would be able to come up with ‘stimulus packages’ for HEIs that needs assistance (financial and non-financial) from the government.